If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -3) = (6x + 4) Reorder the terms: 2(-3 + 4x) = (6x + 4) (-3 * 2 + 4x * 2) = (6x + 4) (-6 + 8x) = (6x + 4) Reorder the terms: -6 + 8x = (4 + 6x) Remove parenthesis around (4 + 6x) -6 + 8x = 4 + 6x Solving -6 + 8x = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 8x + -6x = 4 + 6x + -6x Combine like terms: 8x + -6x = 2x -6 + 2x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + 2x = 4 + 0 -6 + 2x = 4 Add '6' to each side of the equation. -6 + 6 + 2x = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 4 + 6 2x = 4 + 6 Combine like terms: 4 + 6 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| x^2+1800=90x | | 2(3c-6)=5c+8 | | -6-7x+3x=38 | | 5=z+13 | | 8x-3(x-5)=2(x-4)+1 | | -4(3a+5)=-7(2a-5) | | 5(y-3)=3(2y-4) | | x/6+3=6-x/6 | | 3.4y=8.5 | | 6-(x-1)=8 | | 8x^3-y^3= | | 2(3x+2)=(2x-6)+2x | | 5Y-21=2Y | | 5(a-2)=3(4a-5) | | 6p-25=345 | | 3(2y-3)=5(y+1) | | 4(a-7)+4=2a-6 | | 2(x+4)+3=4+7+2x | | -2(3-4x)=7(x+2) | | 0.60x+0.05(12-x)=0.10(-71) | | 33=5v+3 | | 25n=525 | | 4u^3+2u^2-2u+1=0 | | 0.60x+0.05(12-z)=0.10(-71) | | 3y-11=25 | | 8-6d-3+7d=4 | | 3x+5-7-2x=3 | | -2k^2+3k+9=0 | | A+6=-3 | | 5y-3-4y=1 | | 10x+3y=18 | | 3v+7=19 |